2021
DOI: 10.3390/microorganisms9102151
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Topology Prediction of Phage Adhesion Devices Using AlphaFold2: The Case of Two Oenococcus oeni Phages

Abstract: Lactic acid bacteria (LAB) are important microorganisms in food fermentation. In the food industry, bacteriophages (phages or bacterial viruses) may cause the disruption of LAB-dependent processes with product inconsistencies and economic losses. LAB phages use diverse adhesion devices to infect their host, yet the overall picture of host-binding mechanisms remains incomplete. Here, we aimed to determine the structure and topology of the adhesion devices of two lytic siphophages, OE33PA and Vinitor162, infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
(99 reference statements)
0
17
0
1
Order By: Relevance
“…From a structural biology view point, due to their flexibility, these machineries can rarely be studied as a whole (for exceptions see ( Sciara et al, 2010 ; Veesler et al, 2012 )) but mostly as isolated modules. However, we recently showed that the structure of a long and flexible Tal from the Oenococcus oeni phage Vinitor 162 could be predicted with AlphaFold2 ( Goulet and Cambillau, 2021 ).…”
Section: Alphafold2 Opens Up Great Perspectives To Tackle Complex Sam...mentioning
confidence: 99%
See 2 more Smart Citations
“…From a structural biology view point, due to their flexibility, these machineries can rarely be studied as a whole (for exceptions see ( Sciara et al, 2010 ; Veesler et al, 2012 )) but mostly as isolated modules. However, we recently showed that the structure of a long and flexible Tal from the Oenococcus oeni phage Vinitor 162 could be predicted with AlphaFold2 ( Goulet and Cambillau, 2021 ).…”
Section: Alphafold2 Opens Up Great Perspectives To Tackle Complex Sam...mentioning
confidence: 99%
“…Stunning results produced by AlphaFold2 at the CASP14 (Critical Assessment of Techniques for Protein Structure Prediction) contest indicated that deep learning-based methods are now able to predict protein structures with an accuracy comparable, in most cases, to that of experimental structures ( Pereira et al, 2021 ). This important achievement offers great perspectives to the life science community, including experimented structural biologists as well as untrained biologists, to address challenging biological questions ( Goulet and Cambillau, 2021 ; Tunyasuvunakool et al, 2021 ). In particular, the AlphaFold Protein Structure Database ( https://www.alphafold.ebi.ac.uk ), developed by DeepMind and EMBL-EBI, offers open access to structure predictions for the human proteome, for proteins from key model organisms (e.g., Mus musculus , Escherichia coli , Arabidopsis thaliana ), and for proteins from organisms related to global health ( Mycobacterium tuberculosis , Staphylococcus aureus , Trypanosoma cruzi ) ( Tunyasuvunakool et al, 2021 ; Varadi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it is well adapted to predict structures of long, flexible and multi-domain proteins that cannot be analyzed as a whole using experimental approaches such as X-ray crystallography and electron microscopy. Recently, we applied this method to bacterial viruses (bacteriophages) to determine the structures of their whole host-binding machineries with several multi-domain proteins [ 31 , 32 ]. Moreover, as compared with homology modeling, AF2 produces structures that do not suffer from sequence bias, with an estimate of the prediction reliability for each protein residue given by a confidence score, the predicted local distance difference test (pLDDT, from 0 to 100).…”
Section: Introductionmentioning
confidence: 99%
“…This may be an issue in cases where phages do not encode an easily recognizable RBP-encoding gene. To overcome this (at least for phages binding to carbohydrate receptors), identified carbohydrate binding domains (CBMs), responsible for phage host adhesion ( 49 ) and which have been shown to be host specific ( 50 , 51 ), could be employed.…”
Section: Resultsmentioning
confidence: 99%